2005
DOI: 10.1074/jbc.m405970200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced Spermatogenic Cell Apoptosis Occurs via the Mitochondrial Pathway

Abstract: The detrimental effects of estrogen on testicular function provide a conceptual basis to examine the speculative link between increased exposure to estrogens and spermatogenic cell death. Using an in vitro model, we provide an understanding of the events leading to estrogen-induced apoptosis in cells of spermatogenic lineage. Early events associated with estrogen exposure were up-regulation of FasL and increased generation of H 2 O 2 , superoxide, and nitric oxide. The ability of anti-FasL antibodies to preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 49 publications
4
91
0
2
Order By: Relevance
“…Previous studies reported that exposure to non-physiological concentrations of estrogen, testosterone, and estrogenlike chemicals could stimulate the apoptotic pathway in animal germinal cells (Zhou et al 2001, Kim et al 2003, Nair & Shaha 2003, Jung et al 2004, Mishra & Shaha 2005, and cause DNA damage in human sperm (Anderson et al 2003). These reports support the correlations we observed for the European men, e.g.…”
Section: Xenobiotic-induced Receptor Activity Issuessupporting
confidence: 90%
“…Previous studies reported that exposure to non-physiological concentrations of estrogen, testosterone, and estrogenlike chemicals could stimulate the apoptotic pathway in animal germinal cells (Zhou et al 2001, Kim et al 2003, Nair & Shaha 2003, Jung et al 2004, Mishra & Shaha 2005, and cause DNA damage in human sperm (Anderson et al 2003). These reports support the correlations we observed for the European men, e.g.…”
Section: Xenobiotic-induced Receptor Activity Issuessupporting
confidence: 90%
“…Furthermore, Hagen et al (44) reported that 2-methoxyestradiol, a naturally occurring metabolite of E2, inhibits mitochondrial respiration in both intact cells and submitochondrial particles and that this effect is due to inhibition of complex I of the mitochondrial electron transport chain. Recently, Mishra and Shaha (45) reported that estrogen-induced spermatogenic cell apoptosis occurs via the mitochondrial pathway. Although estrogen synthesis occurs in the mitochondria, exogenously added estrogen is also transported to this organelle.…”
Section: Discussionmentioning
confidence: 99%
“…An inverted microscope [(TE-2000E) Nikon] equipped with a RetigaExi camera (Q-imaging) was used to acquire images and coefficient of colocalization was calculated from mask of colocalization using Image-Pro Plus software (Media Cybernetics). For TUNEL labeling, procedure was carried out as described previously (25).…”
Section: Histology and Immunocytochemistrymentioning
confidence: 99%